Investigation of Mechanical Properties of Quicksand Stabilized with Bitumen Emulsion and Reinforced with Waste Polypropylene Fibers and The Effect of Freeze and Thaw on Its Performance - Ghafoori Fard, Zohreh; Khabiri, Mohammad Mehdi; Mohajeri, Ahmad (International Journal of Sustainable Construction Engineering and Technology, 2022)
The existing quicksands in the desert are among the problematic soils whose stabilization has been considered by experts. Emulsion bitumen is one of the environmentally friendly stabilizers of these sands. Also, the method of reinforcement with (fibers) has many advantages due to the increase in soil strength in the same way and the formation of thickness in the soil mass. The aim of this study was to investigate the effect of polypropylene fibers and emulsion bitumen on improving sandy soil properties and the effect of freeze-thaw cycles on the behavior of soils stabilized by these two substances; For this purpose, samples of aeolian sand soil with 0%, 0.25%, 0.5%, 0.75% and 1% waste polypropylene fibers of 0, 5, 10, 15% bitumen emulsion were made and tested for California load-bearing capacity and uniaxial compressive strength. Also, to evaluate the effect of the freeze-thaw cycle, the samples were subjected to uniaxial resistance test after enduring 3 and 7 freeze-thaw cycles. The results show that the addition of fibers and bitumen to the sand first increases the specific gravity and CBR and decreases from one percent onwards by increasing the fibers of these two parameters; It has compressive strength and ultimate strain with increasing fiber percentage; In general, increasing the percentage of fibers from 0 to 1% on average increases the compressive strength by 91% and the final strain by 54% and increasing the percentage of bitumen from 5 to 15% on average increases the compressive strength by 4% and the final strain by 13%. In addition, the results show that the compressive strength of the samples decreases by an average of 15% and 19% after withstanding 3 and 7 freeze-thaw cycles, respectively; however, after enduring 3 and 7 freeze-thaw cycles, the compressive strength increases with increasing the percentage of fibers to 75%.